Ocena dojrzałości szkolnej dzieci z wadą słuchu. Kontrowersje i wyzwania związane z diagnozą psychologiczno-pedagogiczną - Jakoniuk-Diallo, Anna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The start of school education is an important and difficult phase in every child’s life. However with each one of them, we have to deal with the individual pace and specificity of development in each sphere, and even so it is difficult to recognize every child as equally mature as a pupil. Both the evaluation of child progress in the education process and the readiness for school education are made through the prism of linguistic proficiency. In the case of child’s hearing loss, especially when it is congenital or acquired at a very early stage, the development of speech and language is delayed. The determinant of this situation is the lack of access to the audible voice of the guardians. In a slightly different situation there are children with hearing impairment, having deaf parents. These people, from their earliest years, develop their sign language skills, which are primary to them. An increasing number of hearing impaired children go to integration classes in public schools. Does this mean that the psychological and pedagogical diagnosis procedure of the aforementioned group of children, including the study of their school maturity, can be considered appropriate?